MiR-30 disrupts senescence and promotes cancer by targeting both p16INK4A and DNA damage pathways. Issue 42 (18th October 2018) - Su, Weijun; Hong, Lixin; Xu, Xin; Huang, Shan; Herpai, Denise; Li, Lisheng; Xu, Yingxi; Truong, Lan; Hu, Wen-Yuan; Wu, Xiaohua; Xiao, Changchun; Zhang, Wei; et al.
Abstract miR-30 is a microRNA frequently overexpressed in human cancers. However, the biological consequence of miR-30 overexpression in cancer has been unclear. In a genetic screen, miR-30 was found to abrogate oncogenic-induced senescence, a key tumor-suppressing mechanism that involves DNA damage responses, activation of p53 and induction of p16INK4A . In cells and mouse models, miR-30 disrupts senescence and promotes cancer by suppressing 2 targets, CHD7 and TNRC6A. We show that while CHD7 is a transcriptional coactivator essential for induction of p16INK4A in senescent cells, TNRC6A, a miRNA machinery component, is required for expression and functionality of DNA damage response RNAs (DDRNAs) that mediate DNA damage responses and p53 activation by orchestrating histone modifications, chromatin remodeling and recruitment of DNA damage factors at damaged sites. Thus, miR-30 inhibits both p16INK4A and p53, 2 key senescence effectors, leading to efficient senescence disruption. These findings have identified novel signaling pathways mediating oncogene-induced senescence and tumor-suppression, and revealed the molecular and cellular mechanisms underlying the oncogenic activity of miR-30. Thus, the miR-30/CHD7/TNRC6A pathway is potentially a novel diagnostic biomarker and therapeutic target for cancer.